Antibacterial and antishigellosis activity of Xylopia staudtii (engl. & diels), Annonaceae. (15th November 2021) - Pouofo Nguiam, Michel; Njonte Wouamba, Steven Collins; Longo, Frida; Gounoue Kamkumo, Raceline; Donji Kenne Foweda, Larissa; Dzeufiet Djomeni, Paul Desire; Lenta Ndjakou, Bruno; Sewald, Norbert; Fekam Boyom, Fabrice; Kouam Fogue, Simeon; Dimo, Theophile
Abstract: Ethnopharmacological relevance: Xylopia staudtii is a medicinal plant which fruits are traditionally used in western Cameroon as a spice in the preparation of soups known for their abdominal cramp relieving properties. Often identified as Xylopia africana, its bark is used in the treatment of dysentery in Mont Cameroun localities. This plant could therefore contain active ingredients against intestinal pathogens, including Shigella spp, which are responsible of the deathly dysenteric diarrhoea. Aim of the study: This study aims to assess the efficacy of the hydroethanolic extract from Xylopia staudtii bark in immunodepressed mice infected with S higella flexneri . Materials and methods: Qualitative detection of compounds in the crude extract was done using UPLC–DAD–(HR) ESI-MS analysis in an attempt to link the activity to the chemical composition. The MIC and the MBC of the extract was determined using broth dilution method. Shigellosis was induced by intraperitoneal administration of Shigella flexneri to immunodepressed mice pretreated with streptomycin. These infected mice were then treated with the extract (100, 200 and 400 mg/kg), and reference substances (ciprofloxacin and saline). During the 9 days of treatment, animal morphology, fecal pathology and deaths were recorded. At the end of the treatment period, blood and organs were collected from any surviving animals for hematological, biochemical and histopathological analyses. Results: The extract was found to be significantly active, with a bactericidal effect against Shigella and a bacteriostatic effect against Escherichia coli . It was able to reduce and stop the faecal pathology caused by the infection in mice, as well as the rate of deaths which was brought to zero (0) in animal treated at 400 mg/kg. The bacteria load in faeces was reduced by 100% in animal treated at 400 mg/kg. Xylopia staudtii extract elicited anti-inflammatory properties by reducing MPO activity and Lcn2 intestinal level. It also prevents damages in the intestinal tissue and the shortening of colon which characterise Shigella infection. The serum level of ASAT, ALAT, bilirubin, urea and creatinine in animals treated with the extract was similar to those of normal animal used in the study. These activities of the plant may be due at least in part to the presence of ent-kauran type diterpens such as kaurenoic acid identified in the extract. Conclusion: These findings support the usage of Xylopia staudtii as an antimicrobial against bacillary dysentery, making this plant a potential candidate for the formulation of an improved standardized traditional medicine. Graphical abstract: Image 1 Highlights: Immunidepressed mice infected intraperitoneally with S. flexneri exhibit dysentery. X. staudii inhibits deadly symptoms in an immunodepressed mice model of dysentery. X. staudii extract contains ent-kauran diterpens with strong antimicrobial activity. The antidysenteric action of X. staudtii include both local and systemic mechanisms.